Synthesis of some chromium (III) complexes and the use of these complexes as catalyst for the polymerization of alpha-olefins / Che Ibrahim bin Abdullah - Abdullah, Che Ibrahim (2014)
A series of chromium(III) and chromium(III)-iron(III) carboxylate complexes were prepared by heating common chromium(III) and Iron(III) salts in carboxylic acids. The structure of these complexes has been confirmed by X-ray crystallography to give a trinuclear oxo-centred carboxylate. The characterization of complexes was carried out by UV-visible spectroscopy, IR spectroscopy, Thermal analysis (TGA), CHN-elemental analysis and metal content analysis. The complexes contain a triangular arrangement of metal ions connected by a central μ3-oxo atom and bridged with six carboxylate ligands. Each carboxylate anion spans two metal centres at the periphery of the [M3(μ3-O)]6+ core, while H2O ligands occupy the remaining coordination sites on each metal centre to form a coordinated H2O. The coordination around the metal centre is approximately octahedral. These complexes with combination of diethylaluminium chloride as a cocatalyst were used in the polymerization of ethylene to form a heterogeneous catalyst system. The polymerization of ethylene was performed by varying the Al/Cr molar ratio, temperature and changing the catalyst complexes. Kinetic data show that the polymerization of ethylene is a first order reaction. The polymerization of ethylene was modified by introducing SMRCV (natural rubber) into the polymerization system. The polymer produced was characterized by using ATR-IR spectroscopy, TGA, powder XRD and differential scanning calorimetric (DSC).